The effect of cutting height and frequency on the forage, wood and seed production of six Sesbania sesban accessions. Productivity of Sesbania sesban accessions under irrigated conditions - Heering, J.H. (Springer, 1995)
The forage, wood and seed production of six Sesbania sesban accessions was assessed under irrigated conditions for two cutting frequencies and heights. Control trees were left uncut to measure their seed production potential. The trial was conducted over an 18-month period. The fastest growing accession produced almost 10 t/ha total dry matter (DM) after six months of growth, 40 percent of it being leaves. Total DM yield was higher at the six-month cutting interval compared to the three months' interval with yields between 25-42 t/ha/year. Some accessions could not sustain their high level of production but showed drastic drops in yield after repeated cutting. In general leaf DM production increased with increased cutting height. When cut at 150 cm the DM leaf yield at the three-month cutting interval ranged from 9.7-18.2 t/ha. More plants survived at the three-month cutting frequency. Seed yields varied considerably between accessions (0.02-1.56 t/ha total DM comprising 21 percent leaves. Fresh wood biomass ranged between 56.4-138.0 t/ha and seed yields 2.7-6.6 t/ha.